Seeding the future: Accelerating seed system development in Bangladesh - Naher, Firdousi; Spielman, David J. (University Press Limited, 2021)
Evidence accumulated from many developing countries during the past 50 years has demonstrated that yield-enhancing cultivars are vital inputs to sustained agricultural productivity growth, particularly in land-scarce countries where yield growth can only be achieved through intensification (Evenson and Gollin 2003). But sustained productivity growth requires more than just strong scientific expertise and good plant breeding programs. It also requires a modern seed system that has the capacity and infrastructure to multiply, popularize, and distribute these cultivars. And while there are many different designs for a modern seed system, they all share one commonality—they shift seed use practices away from traditional approaches in which farmers select, save, and exchange seeds, to a system that integrates traditional approaches with modern science, public investment, and market signals to provide farmers with more systematic access to improved cultivars and quality seed. Necessarily, this shift also means that seed becomes an economic commodity: it becomes the embodiment of innovative effort undertaken by plant breeders, entrepreneurs, sales representatives, and farmers, across whom the gains from innovation must be distributed in a manner that encourages continuous production and further innovation. It is the role of the policymaker to develop policies that encourage both production and innovation to benefit society.